2019
DOI: 10.1001/jama.2019.2947
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV Preexposure Prophylaxis With Incidence of Sexually Transmitted Infections Among Individuals at High Risk of HIV Infection

Abstract: Emerging evidence suggests that risk of bacterial sexually transmitted infections (STIs) increases among gay and bisexual men following initiation of HIV preexposure prophylaxis (PrEP). OBJECTIVE To describe STI incidence and behavioral risk factors among a cohort of predominantly gay and bisexual men who use PrEP, and to explore changes in STI incidence following PrEP commencement. DESIGN, SETTING, AND PARTICIPANTS The Pre-exposure Prophylaxis Expanded (PrEPX) Study, a multisite, open-label intervention study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
253
16
18

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(329 citation statements)
references
References 23 publications
25
253
16
18
Order By: Relevance
“…We agree, as the respondents point out, that men who have sex with men (MSM) using pre-exposure prophylaxis (PrEP) are a bias group in that they are more likely to have confounding factors contributing to increased rates of sexually transmitted infections (STIs), compared with MSM not using PrEP. Interestingly, recent longitudinal data have suggested that STI rates, particularly rates of rectal STIs, may increase in MSM who start using PrEP [2]. Our data draw attention to local real-life STI rates in a defined population of MSM, and show that MSM using PrEP were more likely to test positive for an STI when they presented to services, which is important when access to testing is decreasing [3,4].…”
Section: Dear Professors Gazzard and Lundgrenmentioning
confidence: 61%
See 1 more Smart Citation
“…We agree, as the respondents point out, that men who have sex with men (MSM) using pre-exposure prophylaxis (PrEP) are a bias group in that they are more likely to have confounding factors contributing to increased rates of sexually transmitted infections (STIs), compared with MSM not using PrEP. Interestingly, recent longitudinal data have suggested that STI rates, particularly rates of rectal STIs, may increase in MSM who start using PrEP [2]. Our data draw attention to local real-life STI rates in a defined population of MSM, and show that MSM using PrEP were more likely to test positive for an STI when they presented to services, which is important when access to testing is decreasing [3,4].…”
Section: Dear Professors Gazzard and Lundgrenmentioning
confidence: 61%
“…Public Health England (PHE) produced mathematical modelling to suggest that their original numbers in IMPACT were an accurate reflection of demand, but have recently doubled the numbers [5]. Anecdotally, we see many MSM who are unable to access PrEP, highlighting that MSM using PrEP make up diverse populations where HIV infection risk may differ as described in the Australian longitudinal study [2].…”
Section: Dear Professors Gazzard and Lundgrenmentioning
confidence: 99%
“…Preliminary indications of risk compensation in PrEP demonstration projects and observational studies are conflicting . This discrepancy might arise from decreased onward transmission of STIs due to more frequent STI screening, whereas ascertainment bias may increase STI detection.…”
Section: Biomedical Interventions For Hiv and Risk Compensationmentioning
confidence: 99%
“…35,36 Behavioral interventions have been shown to be an efficacious method of HIV / sexually transmitted infection (STI) disease prevention in other settings, and they may have positive effects on risk reduction. [37][38][39][40] These approaches are not fail safe, and have not yet been tested in the living donor setting.…”
Section: Components Of Living Donor Evaluation Related To Assessmenmentioning
confidence: 99%